High-temperature and high-humidity resistant laminated solid aluminum electrolytic capacitor and preparation method thereof

CN122991871APending Publication Date: 2026-10-27FUJIAN GUOGUANG XINYE SCI TEC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611394848.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0002]目前,行业内叠层固态铝电解电容器普遍采用环氧树脂模塑料进行单一塑封防护,该技术方案在实际应用中存在三类固有缺陷:(1)、芯子内部的PEDOT:PSS导电高分子表面含有大量亲水磺酸基团与羟基,极易吸附环境水汽,并与氧气发生亲核氧化反应,引发分子链断裂、掺杂阴离子脱附,导致ESR急剧漂移,电化学性能劣化;(2)、环氧树脂塑封体自身存在分子级自由体积,水、氧小分子可通过菲克扩散机制穿透塑封体侵入芯体内部,引发电极腐蚀、内部潮解等失效问题;(3)、环氧树脂与芯子表面材料的热膨胀系数存在数量级差异,在高温塑封、回流焊及冷热循环过程中,界面处会产生巨大剪切应力,导致膜层开裂、界面剥离,最终造成防护体系失效

Benefits of technology

本发明通过在叠层固态铝电解电容器的芯包与环氧树脂塑封体之间设置由内层氟碳钝化层、中层致密阻隔层、外层氟碳缓冲层构成的有机-无机-有机对称三明治结构复合气相沉积阻隔层,可从化学、物理、力学三个维度协同解决现有电容器的失效瓶颈,显著提升产品在高温高湿环境下的长期可靠性,该复合气相沉积阻隔层可完整包覆芯包的顶面、底面、侧面及层间堆叠缝隙,填补了传统封装工艺的防护盲区,实现三维全表面的防护覆盖,并且,现有包封工序的压力直接施加于芯子会造成微裂纹,导致产品漏电流数值偏大,因而传统技术方案需要进行吸湿与老化处理修复氧化铝介质层来提升漏电合格率,而本发明结构的电容器在环氧树脂封装固化后无需额外进行吸湿处理与老化处理,可直接进行成品性能测试,在显著提升产品可靠性的同时简化了生产工序,降低了制造成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122991871A_ABST
    Figure CN122991871A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of solid electrolytic capacitor, in particular to a high-temperature and high-humidity resistant laminated solid aluminum electrolytic capacitor and a preparation method thereof, comprising a core package, the core package is coated with an epoxy resin plastic sealing body outside, the core package is provided with an anode lead and a cathode lead, a composite vapor deposition barrier layer is arranged between the outer surface of the core package and the epoxy resin plastic sealing body, the composite vapor deposition barrier layer comprises an inner fluorocarbon passivation layer, a middle dense barrier layer and an outer fluorocarbon buffer layer from inside to outside, the present application sets the organic-inorganic-organic sandwich structure composite vapor deposition barrier layer composed of the inner fluorocarbon passivation layer, the middle dense barrier layer and the outer fluorocarbon buffer layer between the core package and the epoxy resin plastic sealing body of the laminated solid aluminum electrolytic capacitor, which can solve the failure bottleneck of the existing capacitor from the three dimensions of chemistry, physics and mechanics, and significantly improve the long-term reliability of the product in the high-temperature and high-humidity environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid-state electrolytic capacitor technology, specifically to a high-temperature and high-humidity resistant multilayer solid aluminum electrolytic capacitor and its preparation method. Background Technology

[0002] Currently, epoxy resin molding compound is commonly used for single-layer protection of multilayer solid aluminum electrolytic capacitors in the industry. This technical solution has three inherent defects in practical applications: (1) The PEDOT:PSS conductive polymer surface inside the core contains a large number of hydrophilic sulfonic acid groups and hydroxyl groups, which are very easy to adsorb environmental water vapor and undergo nucleophilic oxidation reaction with oxygen, causing molecular chain breakage and desorption of doped anions, resulting in sharp ESR drift and deterioration of electrochemical performance; (2) The epoxy resin molding compound itself has molecular-level free volume. Water and oxygen molecules can penetrate the molding compound and invade the core through the Fick diffusion mechanism, causing failure problems such as electrode corrosion and internal deliquescence; (3) The thermal expansion coefficients of epoxy resin and core surface materials are orders of magnitude different. During high-temperature molding, reflow soldering and cold and hot cycling, huge shear stress will be generated at the interface, causing the film layer to crack and the interface to peel off, ultimately causing the protection system to fail.

[0003] To address the above issues, existing similar protection technologies have the following main shortcomings: 1. Single-layer inorganic barrier solution: For example, atomic layer deposition (ALD) alumina is used as a moisture barrier layer. Although it has excellent density, the inorganic film is brittle and has thermal expansion mismatch with the organic materials on both sides (conductive silver paste layer, epoxy resin). It is prone to cracking under high temperature cycling and cannot improve the dedoping problem of the conductive polymer itself. 2. Pure organic fluorine-containing coating solution: For example, plasma-enhanced chemical vapor deposition (PECVD) is used to deposit fluorocarbon hydrophobic coatings. Although it has flexibility and hydrophobicity, the film density is insufficient and the water and oxygen barrier capabilities are limited. It cannot block the penetration of small molecules at the mass transfer level. 3. Conventional organic-inorganic dual-layer solution: Existing multi-layer barrier structures are mostly used in planar substrates such as OLEDs and flexible displays. They use a combination of organic silicon and oxides, but are not customized for the three-dimensional stacked structure and heterogeneous interface characteristics of the stacked capacitor core. They cannot simultaneously cover the triple requirements of "polymer passivation - water and oxygen barrier - stress buffer".

[0004] In summary, existing technologies cannot simultaneously solve the three core failure problems of multilayer solid aluminum electrolytic capacitors. There is an urgent need to develop multi-dimensional collaborative packaging and protection technologies to improve the long-term reliability of capacitors in high temperature and high humidity environments. Summary of the Invention

[0005] The purpose of this invention is to provide a high-temperature and high-humidity resistant multilayer solid aluminum electrolytic capacitor and its preparation method. By constructing an organic-inorganic-organic three-layer composite vapor deposition barrier layer, the failure bottleneck of existing products is solved simultaneously from three dimensions: chemical passivation, physical barrier, and mechanical buffering, significantly improving the working reliability under high-temperature and high-humidity environments.

[0006] To achieve the above objectives, the first technical solution provided by this invention is as follows: A high-temperature and high-humidity resistant multilayer solid aluminum electrolytic capacitor and its preparation method are disclosed. The capacitor comprises a core package formed by stacking multiple cores, the core package being encapsulated in an epoxy resin molded body, and the core package having an anode lead and a cathode lead respectively. A composite vapor deposition barrier layer is disposed between the outer surface of the core package and the epoxy resin molded body. The composite vapor deposition barrier layer consists of an inner fluorocarbon passivation layer, a middle dense barrier layer, and an outer fluorocarbon buffer layer from the inside out, forming a symmetrical sandwich structure. The composite vapor deposition barrier layer completely covers the outer surface of the core package and the stacking gaps between the cores, and the exposed metal areas of the anode lead and the cathode lead are not covered.

[0007] Preferably, the inner fluorocarbon passivation layer is a fluorinated organic polymer film prepared by chemical vapor deposition using carbon tetrafluoride as a precursor, and has a thickness of 20~100nm. The surface of the inner fluorocarbon passivation layer is grafted with -CF2 and -CF3 inert hydrophobic functional groups.

[0008] Preferably, the intermediate dense barrier layer is an aluminum oxide thin film prepared by atomic layer deposition, with a thickness of 10~50nm and an amorphous dense structure.

[0009] Preferably, the outer fluorocarbon buffer layer is a fluorinated organic polymer film prepared by chemical vapor deposition using carbon tetrafluoride as a precursor, and has a thickness of 1~10μm, exhibiting a flexible low-modulus structure.

[0010] The second technical solution provided by this invention is: A method for preparing a high-temperature and high-humidity resistant multilayer solid aluminum electrolytic capacitor includes the following steps: S1. Stack the cores according to the set number of layers, solder the anode area of ​​the stacked cores to the anode pins, and use conductive silver paste to attach the cathode area of ​​the stacked cores to the cathode pins. After the conductive silver paste has cured, a core package is formed. S2. The assembled core package is placed in a plasma cleaning chamber for pretreatment. S3. The anode and cathode pin areas of the pretreated core package are shielded, and the shielding area covers all exposed metal surfaces from the root to the end of the anode and cathode pins. S4. On the shielded core package surface, an inner fluorocarbon passivation layer, a middle dense barrier layer, and an outer fluorocarbon buffer layer are deposited sequentially to form a composite vapor deposition barrier layer. S5. After deposition is complete, remove the masking from the pin area to expose the pin area where no film has been deposited. S6. The core package with the composite vapor deposition barrier layer is encapsulated, cured, and molded with insulating resin to form a capacitor.

[0011] Preferably, the pretreatment method for the core package in step S2 is as follows: the core package is placed in a plasma cleaning chamber and argon gas is introduced to perform plasma surface cleaning to remove surface impurities and activate surface groups. The treatment time is 3 to 10 minutes.

[0012] Preferably, in step S3, polyimide tape or a metal masking fixture is used to mask the pins of the core package.

[0013] Preferably, the deposition method of the inner fluorocarbon passivation layer in step S4 is as follows: the pretreated and masked core package is transferred into the chemical vapor deposition reaction chamber, the vacuum is evacuated to a background pressure ≤5Pa, a mixed gas of carbon tetrafluoride and argon is introduced, and the volume ratio of carbon tetrafluoride to argon is 1:3~1:6. The working pressure is controlled at 10~30Pa, the radio frequency power at 50~100W, the deposition temperature at 20~30℃, and the deposition time at 20~30min, so as to form an inner fluorocarbon passivation layer with a thickness of 20~100nm on the surface of the core package.

[0014] Preferably, the deposition method for the intermediate dense barrier layer in step S4 is as follows: the core package after the inner layer deposition is transferred into the atomic layer deposition reaction chamber, using trimethylaluminum as the aluminum source precursor and deionized water as the oxygen source precursor, controlling the deposition temperature at 80~150℃, and preparing an aluminum oxide film by cyclic pulse deposition, with 100~500 cycles, to form an intermediate dense barrier layer with a thickness of 10~50nm; Each deposition cycle consists of: a trimethylaluminum pulse of 0.05–0.2 s, a nitrogen purging of 3–8 s, a water pulse of 0.05–0.2 s, and a nitrogen purging of 3–8 s.

[0015] Preferably, the method for depositing the outer fluorocarbon buffer layer in step S4 is as follows: the core package after the middle layer deposition is transferred back into the chemical vapor deposition reaction chamber, the vacuum is evacuated to a background pressure ≤5Pa, a mixture of carbon tetrafluoride and argon is introduced, and the volume ratio of carbon tetrafluoride to argon is 1:1~1:3. The working pressure is controlled at 20~40Pa, the radio frequency power at 150~300W, and the deposition temperature at 20~30℃. An outer fluorocarbon buffer layer with a thickness of 1-10μm is deposited on the surface of the middle dense barrier layer, thus obtaining a core package with a composite vapor deposition barrier layer.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention addresses the failure bottlenecks of existing capacitors from chemical, physical, and mechanical perspectives by incorporating an organic-inorganic-organic symmetrical sandwich structure composite vapor-deposited barrier layer—comprising an inner fluorocarbon passivation layer, a middle dense barrier layer, and an outer fluorocarbon buffer layer—between the core and epoxy resin encapsulation of a multilayer solid aluminum electrolytic capacitor. This significantly improves the long-term reliability of the product under high temperature and humidity conditions. The composite vapor-deposited barrier layer completely covers the top, bottom, and sides of the core, as well as the interlayer stacking gaps, filling the protection blind spots of traditional encapsulation processes and achieving three-dimensional full-surface protection. Furthermore, the pressure applied directly to the core during existing encapsulation processes can cause micro-cracks, leading to higher leakage current values. Traditional solutions require moisture absorption and aging treatments to repair the alumina dielectric layer and improve leakage current compliance. However, the capacitor structure of this invention eliminates the need for additional moisture absorption and aging treatments after epoxy resin encapsulation and curing, allowing for direct performance testing. This significantly improves product reliability while simplifying the production process and reducing manufacturing costs. Attached Figure Description

[0017] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0018] Figure 1 This is a schematic diagram of the cross-sectional structure of the multilayer solid aluminum electrolytic capacitor in this invention; Figure 2 This is a schematic diagram of the process for preparing the multilayer solid aluminum electrolytic capacitor in this invention.

[0019] The attached diagram lists the components represented by each number as follows: 1. Core package; 2. Epoxy resin encapsulation body; 3. Anode lead; 4. Cathode lead; 5. Inner fluorocarbon passivation layer; 6. Middle dense barrier layer; 7. Outer fluorocarbon buffer layer. Detailed Implementation

[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] like Figure 1-2As shown, a high-temperature and high-humidity resistant multilayer solid aluminum electrolytic capacitor includes a core package 1 formed by stacking multiple cores. The core package 1 is covered with an epoxy resin encapsulator 2. The core package 1 has an anode lead 3 and a cathode lead 4 respectively. A composite vapor deposition barrier layer is disposed between the outer surface of the core package 1 and the epoxy resin encapsulator 2. The composite vapor deposition barrier layer consists of an inner fluorocarbon passivation layer 5, a middle dense barrier layer 6, and an outer fluorocarbon buffer layer 7 from the inside to the outside, forming an organic-inorganic-organic symmetrical sandwich structure. The composite vapor deposition barrier layer completely covers the top, bottom, and sides of the core package 1, as well as the stacking gaps between the cores, achieving three-dimensional full-surface protection. The exposed metal areas of the anode pin 3 and the cathode pin 4 are not covered by the composite vapor deposition barrier layer to ensure the electrical connection performance of the pins.

[0022] The inner fluorocarbon passivation layer 5 is a fluorinated organic polymer film prepared by plasma-enhanced chemical vapor deposition (PECVD) using carbon tetrafluoride as a precursor, with a thickness of 20~100nm. The film surface is grafted with a large number of -CF2 and -CF3 inert hydrophobic functional groups, which can interact with the hydrophilic groups of the conductive polymer on the core surface to achieve chemical passivation and inhibit water vapor adsorption and oxidative dedoping. On the other hand, it can also serve as a flexible transition layer to alleviate the thermal expansion mismatch between the inner organic core and the outer inorganic film and eliminate interfacial stress.

[0023] The middle dense barrier layer 6 is an aluminum oxide film prepared by atomic layer deposition (ALD) process, with a thickness of 10~50nm. It has an amorphous dense structure with almost no molecular-level free volume, which can effectively block the diffusion and penetration paths of small water and oxygen molecules, forming the core physical barrier.

[0024] The outer fluorocarbon buffer layer 7 is a fluorinated organic polymer film prepared by PECVD using carbon tetrafluoride as a precursor. It has a thickness of 1~10μm and a flexible low-modulus structure. This layer is located between the inorganic barrier layer and the epoxy resin encapsulant. It can absorb the interfacial shear stress generated by the thermal expansion and contraction of the epoxy resin encapsulant, avoid film cracking and interfacial peeling, and further block the water vapor path that permeates along the interface.

[0025] The following provides a detailed description of each step in the preparation method described in this invention: S1. Core Packaging Assembly: First, prepare a single core, and according to the set number of layers, weld the anode area of ​​the obtained core to the anode pin 3 of the lead frame. Use conductive silver paste to attach the cathode area of ​​the core to the cathode pin 4 of the lead frame. After the conductive silver paste is cured, multiple cores are stacked together to form core pack 1.

[0026] The specific method for preparing a single-chip is as follows: S11. Cut the aluminum foil into the required size, and then apply a layer of insulating adhesive to the aluminum foil to divide the aluminum foil into a cathode area and an anode area. S12. The formed aluminum foil with the release liner is pretreated, specifically: the formed aluminum foil with the release liner is immersed in the pretreatment solution, and then taken out and dried; the pretreatment solution is composed of a coupling agent, a surfactant and a solvent. The coupling agent is one of silane coupling agent and titanate coupling agent, and the weight percentage of the coupling agent in the pretreatment solution is 0.1 to 5 wt%. The surfactant is selected from any one of ionic surfactant, nonionic surfactant and amphoteric surfactant, and the weight percentage of the surfactant in the pretreatment solution is 0.01 to 5 wt%. The solvent is deionized water, or an organic solvent, or a mixture of deionized water and organic solvent. S13. After the pretreatment is completed, a conductive polymer layer is formed on the surface of the aluminum foil using a chemical polymerization method, and then repair is performed; then another conductive polymer layer is formed on the conductive polymer layer using an electrochemical polymerization process; then a conductive graphite layer is formed on the other conductive polymer layer and cured; after the conductive graphite layer is cured, a conductive silver layer is formed on the conductive graphite layer and cured to obtain the core. S2. Core Packet Surface Pretreatment: The core pack 1, which has been assembled into a stack, is placed in a plasma cleaning chamber. Argon gas is introduced to perform plasma surface cleaning to remove impurities and dust from the surface of the core pack. At the same time, the surface groups are activated to improve the adhesion of the subsequent deposited film. The treatment time is 3~10 minutes.

[0027] S3. Pin area masking: Apply high-temperature resistant polyimide tape to the anode pin 3 and cathode pin 4 areas of the core package 1, or install a special metal mask fixture to mask the pin area; the masking range covers all exposed metal surfaces from the pin root to the pin end, ensuring that the pin area is not covered by the thin film during the subsequent vapor deposition process, and ensuring the electrical connection performance of the pin after plastic encapsulation.

[0028] S4, composite vapor deposition barrier layer deposition S41. Deposition of inner fluorocarbon passivation layer: The pretreated and masked core package is transferred into the PECVD reaction chamber, and the vacuum is evacuated to a background pressure ≤5Pa. A mixture of carbon tetrafluoride and argon is introduced, and the volume ratio of carbon tetrafluoride to argon is controlled to be 1:3~1:6. The working pressure is adjusted to 10~30Pa and the radio frequency power is adjusted to 50~100W. The deposition is carried out at a deposition temperature of 20~30℃ for 20~30min to form an inner fluorocarbon passivation layer 5 with a thickness of 20~100nm on the surface of the core package. The volume ratio range of carbon tetrafluoride to argon and the setting of radio frequency power can regulate the concentration and energy of active fluorocarbon groups in the plasma, ensuring sufficient grafting of -CF2 and -CF3 inert hydrophobic functional groups on the film surface, thus achieving effective passivation of hydrophilic groups on the surface of conductive polymers; the low-temperature deposition conditions of 20~30℃ can avoid damage to the structure and performance of conductive polymers inside the core package by high temperature; the thickness setting of 20~100nm can ensure a complete surface passivation effect while maintaining good film flexibility, giving full play to the stress transition effect between organic and inorganic layers.

[0029] S42. Deposition of the intermediate dense barrier layer: The core package with the inner layer deposited is transferred into the ALD reaction chamber. Trimethylaluminum (TMA) is used as the aluminum source precursor and deionized water is used as the oxygen source precursor. The deposition temperature is controlled at 80~150℃. Alumina film is prepared by cyclic pulse deposition. The single deposition cycle is: TMA pulse 0.05~0.2s, nitrogen purging 3~8s, water pulse 0.05~0.2s, nitrogen purging 3~8s; the number of cycles is controlled at 100~500 times, forming an intermediate dense barrier layer 6 with a thickness of 10~50nm on the core package surface. The deposition temperature of 80~150℃ ensures that trimethylaluminum and the water precursor undergo a sufficient self-limiting reaction on the substrate surface; the precursor pulse duration of 0.05~0.2s and the nitrogen purging duration of 3~8s are matched to avoid precursor residues reacting with the gas phase, forming an amorphous and dense film without pinholes or defects, with atomic-level density, effectively blocking the diffusion of small water and oxygen molecules; the number of cycles of 100~500 corresponds to a film thickness of 10~50nm. This thickness range has both excellent barrier properties and suitable film toughness, avoiding the increased brittleness and cracking problems caused by excessive thickness, while also taking into account production efficiency.

[0030] S43. Deposition of the outer fluorocarbon buffer layer: The core package with the completed middle layer deposition is transferred back into the PECVD reaction chamber, and the vacuum is evacuated to a background pressure ≤5Pa. A mixture of carbon tetrafluoride and argon is introduced, and the volume ratio of carbon tetrafluoride to argon is controlled to be 1:1~1:3. The working pressure is adjusted to 20~40Pa and the radio frequency power is adjusted to 150~300W. Deposition is carried out at a deposition temperature of 20~30℃ until an outer fluorocarbon buffer layer 7 with a thickness of 1~10μm is formed on the surface of the middle dense barrier layer. Finally, a core package 1 with a complete composite vapor deposition barrier layer is obtained.

[0031] Among them, the relatively higher working gas pressure and radio frequency power settings can improve the diffraction and encapsulation capabilities of the plasma, achieve complete filling of the core package side and interlayer stacking gaps, and eliminate protection blind spots; the gas source ratio and deposition conditions of 1:1 to 1:3 can form a flexible, low-modulus, thick fluorocarbon film. The thickness of 1 to 10 μm can fully absorb the interfacial shear stress caused by the difference in thermal expansion coefficients between the epoxy resin encapsulator and the core package, buffer the interfacial deformation during the hot and cold cycle, avoid film cracking and interfacial peeling, and further block the water vapor path that permeates along the interface.

[0032] S5. Mask Removal: After deposition is complete, remove the core package and remove the polyimide tape or metal mask fixture from the pin area to expose the pin area where no film has been deposited. If there is a small amount of film residue at the pin root, it can be removed by mechanical polishing or laser cleaning to ensure that the subsequent plastic encapsulation and electrical connection of the pin are not affected.

[0033] S6. Molding and curing: The core package 1 with the composite vapor deposition barrier layer is molded and encapsulated with epoxy resin. After encapsulation, it is cured at 100~200℃ for 0.5~24 hours. After molding, the final capacitor product is formed.

[0034] The capacitors prepared using this invention do not require additional moisture absorption or aging treatment after molding and curing, and can be directly tested for electrical performance, thus simplifying the production process.

[0035] To verify the technical effect of the present invention, the following embodiments were set up for comparative testing with a control group:

[0036] Example 1: S1: Prepare a core package with specifications of 2.5V / 470μF; S2: Clean with argon plasma for 5 minutes; S3: Use polyimide tape to shield the pin area; S4: Deposition of inner fluorocarbon passivation layer: The volume ratio of carbon tetrafluoride to argon is 1:4, the working pressure is 20Pa, the radio frequency power is 80W, the deposition temperature is 25℃, the deposition time is 25min, and the film thickness is about 80nm. S5: Remove mask; S6: Place the deposited core package into an injection mold, encapsulate it with epoxy resin, cure it at 175°C for 2 hours after encapsulation, and then perform molding treatment to obtain the finished capacitor.

[0037] Example 2: S1: Prepare a core package with specifications of 2.5V / 470μF; S2: Clean with argon plasma for 5 minutes; S3: Use polyimide tape to shield the pin area; S4: Deposition of inner fluorocarbon passivation layer: The volume ratio of carbon tetrafluoride to argon is 1:4, the working pressure is 20Pa, the radio frequency power is 80W, the deposition temperature is 25℃, the deposition time is 25min, and the film thickness is about 80nm. S5: Deposition of a dense barrier layer in the middle layer: using trimethylaluminum and deionized water as precursors, deposition temperature 120℃, 200 cycles, film thickness approximately 30nm; S6: Remove mask; S7: After epoxy resin encapsulation, the capacitor is cured at 175°C for 2 hours, followed by molding to obtain the finished capacitor.

[0038] Example 3 (Preferred Example): S1: Prepare a core package with specifications of 2.5V / 470μF; S2: Clean with argon plasma for 5 minutes; S3: Use polyimide tape to shield the pin area; S4: Deposition of inner fluorocarbon passivation layer: The volume ratio of carbon tetrafluoride to argon is 1:4, the working pressure is 20Pa, the radio frequency power is 80W, the deposition temperature is 25℃, the deposition time is 25min, and the film thickness is about 80nm. S5: Deposition of a dense barrier layer in the middle layer: using trimethylaluminum and deionized water as precursors, deposition temperature 120℃, 200 cycles, film thickness approximately 30nm; S6: Deposition of outer fluorocarbon buffer layer: The volume ratio of carbon tetrafluoride to argon is 1:2, the working pressure is 30Pa, the radio frequency power is 200W, the deposition temperature is 25℃, and the film thickness is about 3μm. S7: Remove mask; S8: After epoxy resin encapsulation, the capacitor is cured at 175°C for 2 hours, followed by molding to obtain the finished capacitor.

[0039] Example 4 (Parameter Upper Limit Example) The remaining steps are the same as in Example 3, except that the deposition parameters are adjusted: Inner fluorocarbon passivation layer: the volume ratio of carbon tetrafluoride to argon is 1:5, the working pressure is 30Pa, the radio frequency power is 100W, the deposition temperature is 30℃, the deposition time is 30min, and the film thickness is about 100nm. Middle dense barrier layer: deposition temperature 150℃, 500 cycles, film thickness approximately 50nm; Outer fluorocarbon buffer layer: The volume ratio of carbon tetrafluoride to argon is 1:3, the working pressure is 40Pa, the radio frequency power is 300W, the deposition temperature is 30℃, and the film thickness is approximately 10μm.

[0040] Example 5 (Parameter Lower Limit Example) The remaining steps are the same as in Example 3, except that the deposition parameters are adjusted: Inner fluorocarbon passivation layer: the volume ratio of carbon tetrafluoride to argon is 1:3, the working pressure is 10Pa, the radio frequency power is 50W, the deposition temperature is 20℃, the deposition time is 20min, and the film thickness is about 20nm. Middle dense barrier layer: deposition temperature 80℃, 100 cycles, film thickness approximately 10nm; Outer fluorocarbon buffer layer: The volume ratio of carbon tetrafluoride to argon is 1:1, the working pressure is 20Pa, the radio frequency power is 150W, the deposition temperature is 20℃, and the film thickness is approximately 1μm.

[0041] control group S1: Prepare a core package with specifications of 2.5V / 470μF; S2: Without any coating treatment, the capacitor is directly encapsulated with epoxy resin and cured at 175°C for 2 hours, followed by molding to obtain the finished capacitor. S3: Perform moisture absorption and aging treatment on the capacitor: moisture absorption treatment temperature 68℃, humidity 90%, moisture absorption time 120 minutes; aging treatment first increases the voltage to 2.2V at room temperature at a rate of 0.1V / min, ages at room temperature for 30 minutes, and then ages at 90℃ for 400 minutes.

[0042] The above samples were subjected to reliability tests at 85℃ / 85%RH for 1000 hours and at 125℃ for 5500 hours, respectively. The capacitance (Cap), loss tangent (DF), equivalent series resistance (ESR), leakage current (LC), and capacitance change rate (ΔC / C) were tested. The test results are shown in Table 1-2 below: Table 1. Product data after 1000h test at 85℃ / 85%RH (Specification: 2.5V 470μF)

[0043] Table 2. Product data after 5500 hours of testing at 125℃ (Specification: 2.5V 470μF)

[0044] Test data shows that, compared with the control group, the capacitors of each embodiment of the present invention exhibit higher capacitance retention, significantly reduced DF, ESR, and leakage current, and a substantial decrease in performance degradation after high temperature and humidity and long-term high temperature testing. Specifically, the ESR of Example 2 under long-term high-temperature reliability is higher than that of Example 1, indicating that the thermal expansion mismatch between the core and epoxy resin introduces interfacial stress when the dense middle barrier layer is absent, thus confirming the necessity of the outer fluorocarbon buffer layer. Furthermore, Examples 3-5, employing a three-layer composite barrier structure, show particularly outstanding results, with all performance indicators far exceeding the specification limits, verifying that the three-layer sandwich structure of the present invention can synergistically improve the high temperature and humidity resistance reliability of the capacitor from chemical, physical, and mechanical dimensions.

[0045] The present invention also has several alternative solutions that can achieve the same technical effect: 1. Precursor substitution: The precursor of the fluorocarbon layer can be replaced with short-chain fluorocarbon gases such as tetrafluoroethylene and hexafluoroethane, and fluorinated organic polymer films can also be prepared. 2. Material substitution: The middle inorganic barrier layer can be replaced with dense inorganic materials such as titanium oxide (TiO2), hafnium oxide (HfO2), and silicon nitride (Si3N4) that can be deposited by ALD process to achieve a similar barrier effect; 3. Process expansion: The number of alternating layers of "organic-inorganic" can be increased according to product reliability requirements to further improve barrier performance; 4. Equipment compatibility: Integrated vapor deposition equipment can be used to complete the continuous deposition of three-layer films, simplifying the process and improving mass production efficiency.

[0046] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that variations may be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A high-temperature and high-humidity resistant multilayer solid aluminum electrolytic capacitor, comprising a core package (1) formed by stacking multiple cores, wherein the core package (1) is externally covered with an epoxy resin encapsulant (2), and the core package (1) is respectively provided with an anode lead (3) and a cathode lead (4), characterized in that: A composite vapor deposition barrier layer is provided between the outer surface of the core package (1) and the epoxy resin encapsulant (2). The composite vapor deposition barrier layer consists of an inner fluorocarbon passivation layer (5), a middle dense barrier layer (6), and an outer fluorocarbon buffer layer (7) from the inside to the outside, forming a symmetrical sandwich structure. The composite vapor deposition barrier layer completely covers the outer surface of the core package (1) and the stacking gap between the cores, and the exposed metal areas of the anode pin (3) and the cathode pin (4) are not covered.

2. The high-temperature and high-humidity resistant multilayer solid aluminum electrolytic capacitor according to claim 1, characterized in that: The inner fluorocarbon passivation layer (5) is a fluorinated organic polymer film prepared by chemical vapor deposition using carbon tetrafluoride as a precursor, and has a thickness of 20~100nm. The inner fluorocarbon passivation layer (5) has -CF2 and -CF3 inert hydrophobic functional groups grafted onto its surface.

3. The high-temperature and high-humidity resistant multilayer solid aluminum electrolytic capacitor according to claim 1, characterized in that: The intermediate dense barrier layer (6) is an aluminum oxide thin film prepared by atomic layer deposition, with a thickness of 10~50nm and an amorphous dense structure.

4. The high-temperature and high-humidity resistant multilayer solid aluminum electrolytic capacitor according to claim 1, characterized in that: The outer fluorocarbon buffer layer (7) is a fluorinated organic polymer film prepared by chemical vapor deposition with carbon tetrafluoride as a precursor, and has a thickness of 1~10μm and a flexible low modulus structure.

5. A method for preparing a high-temperature and high-humidity resistant multilayer solid aluminum electrolytic capacitor as described in claim 1, characterized in that, Includes the following steps: S1. Stack the cores according to the set number of stacking layers, weld the anode area of ​​the stacked cores to the anode pin (3), and use conductive silver paste to attach the cathode area of ​​the stacked cores to the cathode pin (4), and wait for the conductive silver paste to cure to form a core package (1). S2. The core package (1) that has been assembled into a stack is placed in a plasma cleaning chamber for pretreatment; S3. The anode pin (3) and cathode pin (4) areas of the pretreated core package (1) are shielded, and the shielding area covers all exposed metal surfaces from the root of the anode pin (3) and the cathode pin (4) to the pin end. S4. On the surface of the shielded core package (1), an inner fluorocarbon passivation layer (5), a middle dense barrier layer (6), and an outer fluorocarbon buffer layer (7) are deposited sequentially to form a composite vapor deposition barrier layer. S5. After deposition is complete, remove the masking from the pin area to expose the pin area where no film has been deposited. S6. The core package (1) with the composite vapor deposition barrier layer is encapsulated, cured and molded with insulating resin to form a capacitor.

6. The method for preparing a high-temperature and high-humidity resistant multilayer solid aluminum electrolytic capacitor according to claim 5, characterized in that: The pretreatment method of the core package (1) in step S2 is as follows: the core package (1) is placed into the plasma cleaning chamber and argon gas is introduced to perform plasma surface cleaning to remove surface impurities and activate surface groups. The treatment time is 3~10 min.

7. The method for preparing a high-temperature and high-humidity resistant multilayer solid aluminum electrolytic capacitor according to claim 5, characterized in that: In step S3, polyimide tape or metal masking fixtures are used to shield the pins of the core package (1).

8. The method for preparing a high-temperature and high-humidity resistant multilayer solid aluminum electrolytic capacitor according to claim 5, characterized in that: The deposition method of the inner fluorocarbon passivation layer (5) in step S4 is as follows: the pretreated and masked core package is transferred into the chemical vapor deposition reaction chamber, the vacuum is drawn to the background pressure ≤5Pa, a mixed gas of carbon tetrafluoride and argon is introduced, and the volume ratio of carbon tetrafluoride to argon is 1:3~1:

6. The working pressure is controlled at 10~30Pa, the radio frequency power at 50~100W, the deposition temperature at 20~30℃, and the deposition time at 20~30min, so that an inner fluorocarbon passivation layer (5) with a thickness of 20~100nm is formed on the surface of the core package.

9. The method for preparing a high-temperature and high-humidity resistant multilayer solid aluminum electrolytic capacitor according to claim 5, characterized in that: The deposition method of the intermediate dense barrier layer (6) in step S4 is as follows: the core package after the inner layer deposition is transferred into the atomic layer deposition reaction chamber, using trimethylaluminum as the aluminum source precursor and deionized water as the oxygen source precursor, controlling the deposition temperature at 80~150℃, and preparing aluminum oxide thin film by cyclic pulse deposition, with a cycle number of 100~500 times, to form an intermediate dense barrier layer (6) with a thickness of 10~50nm. Each deposition cycle consists of: a trimethylaluminum pulse of 0.05–0.2 s, a nitrogen purging of 3–8 s, a water pulse of 0.05–0.2 s, and a nitrogen purging of 3–8 s.

10. The high-temperature and high-humidity resistant multilayer solid aluminum electrolytic capacitor and its preparation method according to claim 5, characterized in that: The method for depositing the outer fluorocarbon buffer layer (7) in step S4 is as follows: the core package that has completed the middle layer deposition is transferred back into the chemical vapor deposition reaction chamber, the vacuum is drawn to the background pressure ≤5Pa, a mixed gas of carbon tetrafluoride and argon is introduced, and the volume ratio of carbon tetrafluoride to argon is 1:1~1:

3. The working pressure is controlled at 20~40Pa, the radio frequency power is 150~300W, the deposition temperature is 20~30℃, and the outer fluorocarbon buffer layer (7) with a thickness of 1-10μm is formed on the surface of the middle dense barrier layer, thus obtaining the core package (1) with the composite vapor deposition barrier layer.